The influence of training load on markers of fatigue in junior male semi-elite sailors. - Bateup, B.; Thornton, H.; Withers, S.; Duthie, G. (Journal of Australian Strength and Conditioning, 2016)
Sailing is a physically demanding sport, however there is currently limited research that has examined how sailing influences various measures of fatigue. Specifically, time spent in the up-wind sailing position known as hiking is physically taxing, therefore we aimed to investigate the influence of hiking time on changes in countermovement jump (CMJ) and grip strength tests from pre to post training.